The “Anarchy” of King Arthur’s Beginnings: The Politics that Created the Arthurian Tradition - Andrew D Pringle (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2019)
“The ‘Anarchy’ of King Arthur’s Beginnings: The Politics that Created the Arthurian Tradition” examines Geoffrey of Monmouth’s Historia regum Brittaniae in a political and historical context to illuminate the 12th-century politics that started the Arthurian tradition and show how those politics influenced later works about the legendary king. Based on literary and historical research, this paper covers the transmission of politics in the Historia in three sections: a summary of the politics during the time Geoffrey wrote the Historia, an examination of the way those politics were integrated into the Historia, and finally a consideration of how the political themes of the chronicle have been transformed and changed through adaptation. This paper sets out to show the influence the Historia’s politics had on the King Arthur tradition and to argue that some features of those politics remain within the Arthurian literary tradition.
Keywords: Geoffrey of Monmouth; civil war; literature; politics; Norman culture